The geographical distribution of( Plantago spp.) in the west of Basra Governorate and its economic benefits - Hashim Hussein Ali Al-Tamimi , Prof. Assist .Dr. Muhammad (Basra studies journal, 2024)
The study focused on the Zubair Desert, located in the western part of Basra Governorate. It examined the characteristics of the plant genus Plantago spp. and the geographical factors influencing its presence and spatial distribution within the region. This includes species such as Plantago boisseri (commonly known as ewe’s head), Plantago ovata Forssk. (Al-Sakhla), Plantago lanceolata L., and Plantago amplexicaulis Cav. The study also explored the economic importance of these plants, particularly their medicinal uses. Notable benefits include prevention of digestive issues, treatment of irritable bowel syndrome, promotion of heart and circulatory system health, weight management, and diabetes prevention. The study concluded with recommendations, including cultivating and optimizing the plant’s productivity by creating suitable growth environments for economic benefit. Another recommendation emphasized avoiding the use of these plants for treatment without proper knowledge or specialist consultation, due to the risk of significant adverse effects from misuse.